Seasonal variation of columnar aerosol optical properties over Athens, Greece, based on MODIS data - Kosmopoulos, P. G.; Kaskaoutis, D. G.; Nastos, P. T.; Kambezidis, H. D. (Remote Sensing of Environment, 2008)
A long-term (2000–2005) data set of aerosol optical properties obtained from the Moderate Resolution Imaging Spectroradiometer (MODIS) is analyzed focusing on the Greater Athens Area in the Eastern Mediterranean region. The MODIS aerosol optical depth standard product (AOD at 550 nm) and its respective ratio attributed to fine-mode particles (FM) are employed to evaluate the inter-annual and seasonal variability of the aerosol properties over Athens. Based on AOD550 and FM values three specific aerosol types are discriminated corresponding to different aerosol load and optical properties. The aerosol types considered correspond to urban/industrial aerosols, coarse-mode particles and clean maritime conditions. This study focuses on the seasonal and year-to-year fluctuation of the number of occurrences as well as the AOD550 and FM values of each aerosol type. The coarse-mode particles are observed mainly in the summer, while spring is the most favorable season for the occurrence of urban/industrial aerosols. On the other hand, clean maritime conditions occur mainly in the winter. The AOD550 values for the coarse-mode particles are higher in spring, while the urban/industrial and clean maritime aerosols exhibit slightly higher values in the summer. The seasonal distribution of the aerosol properties is related to anthropogenic and dust emissions in the spring/summer period, but is modified by atmospheric dispersion and precipitation in late autumn/winter. The main conclusion of the study is that the coarse-mode particles exhibit much stronger interannual and seasonal variability compared to the urban/industrial aerosols. Finally, three cases corresponding to each aerosol type are analyzed with the aid of synoptic weather maps, air mass trajectories and MODIS data.